Earth Observation for Earth System Science Education: the MICE activity - Assimakopoulou, P.; Nastos, P.; Vassilakis, Emm.; Antonarakou, A. (15th International Congress of the Geological Society of Greece, 2019)
Developing educational material based on satellite remote sensing technologies, information and methods, is a key trend in modern pedagogy of Earth System Sciences. Here, we present “MICE”, a classroom activity on Melting ICe Effects, that utilizes remote sensing information to demonstrate the value of Earth Observation (EO) as a context to teach the STEM (Science, Technology, Engineering and Mathematics) school curriculum. The activity focuses on the subject of polar ice melting as a main climate change effect and the different impact of land and sea ice melting on sea level rise. Students, have the opportunity to discover the above experimentally and subsequently, to observe the diachronic change on polar ice through sequences of satellite images and discover the positive climate feedback on global warming. The activity was translated and adapted to the Greek curriculum from the freely available classroom resources of the European Space Agency (ESA, “Teach with Space” collection). MICE, has been enriched with Greek scientific material, including up-to-date information on climate impacts, localized for the extended region. As part of an evolutionary process, the activity was pilot-tested with 6th grade primary school students and adjusted according to the trial findings. This work is considered as the first step towards the development of original Greek educational material that will utilize EO and climate change as the context to teach STEM school curriculum, capitalizing on the pedagogical role satellite remote sensing and inquiry-based teaching methods, can play.